Deforestation: Mapping the Impact on Wildlife - Ahlawat , Sonika (Trinity Law Review, 2024)
In the era of globalization, countries are making significant progress for the benefit  of their populations. Governments are taking necessary steps to advance and provide  facilities for the comfort of their citizens. However, amidst this progress, the welfare  of wildlife is often overlooked. From a legal standpoint, wildlife lacks rights against  governmental actions, and there is no provision for them to appeal against decisions,  as they are not recognized as human beings.  This article explores the multifaceted impact of deforestation on wildlife, emphasiz ing the profound consequences of habitat loss, disruption of food chains, and the sub sequent decline in biodiversity. As forests are systematically cut down, the intricate  ecosystems that support various species face severe challenges, leading to number  declines and, in some cases, species extinction. The article underscores the inter connectedness of ecosystems and the far-reaching implications of deforestation on  climate change. In response to these challenges, conservation strategies such as sus tainable forestry practices, habitat protection, and the creation of wildlife corridors  are discussed. In conclusion, the article calls for heightened awareness and collective  action to preserve biodiversity and foster a harmonious coexistence between human  activities and the natural world.
Keywords: Wildlife; extinction; habitat; climate change; ecosystem